The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnmol.2021.747855
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Changes in Prader-Willi Syndrome Neurons Reveals Clues About Increased Autism Susceptibility

Abstract: Background: Prader-Willi syndrome (PWS) is a neurodevelopmental disorder characterized by hormonal dysregulation, obesity, intellectual disability, and behavioral problems. Most PWS cases are caused by paternal interstitial deletions of 15q11.2-q13.1, while a smaller number of cases are caused by chromosome 15 maternal uniparental disomy (PW-UPD). Children with PW-UPD are at higher risk for developing autism spectrum disorder (ASD) than the neurotypical population. In this study, we used expression analysis of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 77 publications
(106 reference statements)
0
14
0
Order By: Relevance
“…While it has long been understood that perturbations of the chr15q11-13 region cause PWS, it is unclear if the genes included in the deletions are directly related to PWS phenotypes, if genes regulated by them are to blame, or if it is some combination of these effects. Multiple studies have atempted to address this issue by characterizing gene expression in postmortem PWS brain tissues and neurons differentiated from PWS patient-derived pluripotent stem cell lines to identify genes dysregulated in this disorder (Bochukova et al, 2018; Falaleeva et al, 2015; Huang et al, 2021; Sledziowska et al, 2023; Victor et al, 2021). While these studies indicate gene expression is indeed dysregulated in PWS patient samples, our analysis here showed few genes had consistent dysregulation across a subset of these studies (Supplemental Figure 1A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has long been understood that perturbations of the chr15q11-13 region cause PWS, it is unclear if the genes included in the deletions are directly related to PWS phenotypes, if genes regulated by them are to blame, or if it is some combination of these effects. Multiple studies have atempted to address this issue by characterizing gene expression in postmortem PWS brain tissues and neurons differentiated from PWS patient-derived pluripotent stem cell lines to identify genes dysregulated in this disorder (Bochukova et al, 2018; Falaleeva et al, 2015; Huang et al, 2021; Sledziowska et al, 2023; Victor et al, 2021). While these studies indicate gene expression is indeed dysregulated in PWS patient samples, our analysis here showed few genes had consistent dysregulation across a subset of these studies (Supplemental Figure 1A).…”
Section: Discussionmentioning
confidence: 99%
“…Since the function of SNORD116 thus far has remained elusive, much effort has recently been expended to identify gene expression paterns that are dysregulated in PWS. Several studies have compared gene expression between tissue or cell lines derived from PWS patients and those from unrelated controls (Bochukova et al, 2018; Falaleeva et al, 2015; Huang et al, 2021; Sledziowska et al, 2023; Victor et al, 2021). While each of these studies identified numerous genes with distinct expression paterns in the PWS context, a coherent set of consistently dysregulated disease relevant genes has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these findings suggest a real relationship between ASD and mitochondrial diseases. Interestingly, some imprinted genes also appear to affect mitochondrial function (Bressan and Kramer 2021 ; Panov et al 2020 ; Urraca et al 2013 ; Victor et al 2021 ; Yazdi et al 2013 ).…”
Section: Identified Parent-of-origin Effects In Asdmentioning
confidence: 99%
“…Our group and others have had success modeling neurogenetic syndromes using these stem cells differentiated to neuronal cultures ( 37 41 ). Using this unique patient-derived stem cell model, we have observed molecular signatures and cellular phenotypes of various syndromes in primary neurons including Prader-Willi, Angelman, and Duplication 15q syndromes ( 42 44 ). Here we utilize this system to differentiate patient-derived DPSC lines to neuronal cultures for RNAseq in order to identify the molecular similarities and find genotype/phenotype correlations among ROHHAD, CCHS and PWS.…”
Section: Introductionmentioning
confidence: 99%